Physical Education Teacher Professional Competence in Traditional Game Learning of Elementary Schools in Kudus (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Teacher is the main practitioner in the process of educational renewal to meet the needs of human resource quality that can play their roles professionally in the community. The purpose of the results in this research is to find out physical education teacher professional steps in the implementation of traditional games learning in elementary school when applying innovative methods in physical education learning. Research method used qualitative descriptive with the subjects were PE teachers, headmasters and students, there were 18 respondents consisted of 6 teachers, 6 headmasters and 6 students, and the results show that through traditional games learning that required a lot of movements was able to be used as a physical education learning material. Traditional games also had various values such as sportsmanship, honesty, precision, agility, accuracy in determining steps, and ability to work together in groups.